A Journey Into The Unknown: Moving Beyond Behaviourist - David Costello (Canadian Society for Studies in Education, 2014)
I was not the teacher that I wanted to be. My reading instruction was not meeting my own expectations. As a teacher and graduate student, I was interested in finding out more about reading instruction and student reading comprehension. I wanted to make the connection between theory and my own practice, which led me to question how I could incorporate student engagement into my reading instruction. This teacher research study examines the influence of mandated literacy curricula on student reading actions and experiences. The research findings attained through teacher journaling provide insight into how this reflective practice may transform reading instruction, and how these transformed practices may enable students to be active participants in the classroom while deepening their comprehension. This research study provides teachers with an example of how reading instructional practices based on student learning increases the likelihood of student participation and comprehension.